THE NEXUS BETWEEN TAX POLICY DYNAMICS AND THE COMPLEXITIES OF POLITICAL AND SOCIO-ECONOMIC STABILITY IN INDONESIA - Antoni Antoni (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Tax policy plays a crucial role in shaping the socioeconomic landscape of nations, reflecting political ideologies and priorities while impacting political dynamics and socioeconomic stability. This paper comprehensively analyzes the intricate relationship between tax policy dynamics and the complexities of political and socio-economic stability in Indonesia. By examining the influence of political ideologies on tax policy formulation and the role of political institutions in shaping tax policies, this study elucidates the underlying mechanisms driving tax policy decisions. Furthermore, empirical insights from studies on tax policy in Indonesia shed light on the impact of tax policies on income distribution, economic growth, and social welfare outcomes. Drawing on theoretical frameworks and comparative analyses, this paper identifies key challenges facing tax policy implementation and offers recommendations to fortify tax policy frameworks, foster fiscal sustainability, and promote inclusive development in Indonesia.